2020
DOI: 10.2174/0929867325666180330092607
|View full text |Cite
|
Sign up to set email alerts
|

Terpenes, Phenylpropanoids, Sulfur and Other Essential Oil Constituents as Inhibitors of Cholinesterases

Abstract: Essential oils constituents are a diverse family of low molecular weight organic compounds with comprehensive biological activity. According to their chemical structure these active compounds can be divided into four major groups: terpenes, terpenoids, phenylpropenes, and "others". In addition, they may contain diverse functional groups according to which they can be classified as hydrocarbons (monoterpenes, sesquiterpenes, and aliphatic hydrocarbons); oxygenated compounds (monoterpene and sesquiterpene alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 102 publications
0
49
1
Order By: Relevance
“…For S. transsylvanica and S. glutinosa AchE inhibitory potential was comparable (1.72 ± 0.09 mg GALAE/g extract and 1.70 ± 0.16 mg GALAE/g extract), while the anti-BchE activity was almost three-fold higher for S. transsylvanica (1.43 ± 0.19 mgGALAE/g extract) than for S. glutinosa (0.52 ± 0.10 mgGALAE/g extract). The obtained results could be linked to the presence in high amounts of some phenolics (i.e., catechin, rutin) and monoterpenoidic (i.e., carvacrol) compounds (previously reported for their BChE inhibitory potential [34,39,40]) in the extract of S. transsylvanica.…”
Section: In Vitro Evaluation Of Enzyme Inhibitory Properties Of the Ementioning
confidence: 59%
“…For S. transsylvanica and S. glutinosa AchE inhibitory potential was comparable (1.72 ± 0.09 mg GALAE/g extract and 1.70 ± 0.16 mg GALAE/g extract), while the anti-BchE activity was almost three-fold higher for S. transsylvanica (1.43 ± 0.19 mgGALAE/g extract) than for S. glutinosa (0.52 ± 0.10 mgGALAE/g extract). The obtained results could be linked to the presence in high amounts of some phenolics (i.e., catechin, rutin) and monoterpenoidic (i.e., carvacrol) compounds (previously reported for their BChE inhibitory potential [34,39,40]) in the extract of S. transsylvanica.…”
Section: In Vitro Evaluation Of Enzyme Inhibitory Properties Of the Ementioning
confidence: 59%
“…As illustrated in the PCA plot, enzymatic inhibition activity seems to be associated with the presence of C15 terpenoids (such as γ-selinene or Guaiol). In this regard, relationship between terpenoid molecular structures and AChE/BChE inhibition activity has been reported in literature 33 . In agreement with our results, some studies have shown that hydrocarbon sesquiterpenes like valencene are active against cholinesterase enzymes 33 .…”
Section: Relationship Between Bioactivity and Chemical Compositionmentioning
confidence: 99%
“…In this regard, relationship between terpenoid molecular structures and AChE/BChE inhibition activity has been reported in literature 33 . In agreement with our results, some studies have shown that hydrocarbon sesquiterpenes like valencene are active against cholinesterase enzymes 33 . In addition, the presence of oxygenated functional group in terpenoidal structure (e.g.…”
Section: Relationship Between Bioactivity and Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we verify the versatility of the method in reactions using propargylic sulfides and selenides as starting materials, and good yields of the desired products 5 q and 5 r could be obtained ( Figure 2, compounds 5 q and 5 r). It is known, compounds containing aldehydes or even benzaldehydes have been presenting interesting biological action, such as: antimicrobial and anticancer activity, [27] cholinesterase inhibition [28] and memory and learning improvement. [29] Considering the presented potential of the compounds containing aldehydes and triazole groups in the literature, new compounds containing both structures in the chemical composition would be an advantageous strategy to search for new bioactive molecules, or even new treatments for neurodegenerative diseases.…”
Section: Chemmedchemmentioning
confidence: 99%